Imatinib combined with mitoxantrone/etoposide and cytarabine is an effective induction therapy for patients with chronic myeloid leukemia in myeloid blast crisis - Frühauf, Stefan; Topaly, Julian; Buß, Eike Christian; Fischer, Thomas; Ottmann, Oliver G.; Emmerich, Bertold; Müller, Martin Christian; Schuld, Peter; Balleisen, Leopold; Hehlmann, Rüdiger; Ho, Anthony Dick; Hochhaus, Andreas (Cancer, 2007)
BACKGROUND Despite advances in drug therapy and allogeneic stem cell transplantation (allo-SCT), the prognosis of patients with chronic myeloid leukemia (CML) in blast crisis remains poor. Imatinib has demonstrated synergistic effects in vitro with mitoxantrone, etoposide, and cytarabine. METHODS A Phase I/II trial was performed in patients with CML myeloid blast crisis. Patients were treated with imatinib + mitoxantrone/etoposide in four cohorts: mitoxantrone 10 mg/m2/day and etoposide 100 mg/m2/day for 2 or 3 consecutive days and imatinib 600 mg/day from Day 15 (cohorts 1 and 2) or from Day 1 (cohorts 3 and 4). After hematologic reconstitution after the cytopenic phase, cytarabine was given at a dose of 10 mg/m2/day in addition to imatinib as maintenance treatment. RESULTS A total of 16 patients were available for analysis, median age 59 years (range, 37-74). All patients who received more intensive induction treatment (cohorts 3 and 4, n = 7) achieved a hematologic response (HR). In contrast, HR was achieved in only 6 of 9 patients treated in cohorts 1 and 2. The induction treatment was well tolerated. Six patients who achieved HR received an allo-SCT with myeloablative conditioning. The median survival in the transplant group was 16.2 months vs 4.7 months in the group with conventional treatment only (P = .067). CONCLUSIONS The combination of mitoxantrone/etoposide and imatinib is well tolerated, with mild nonhematologic toxicity even in older patients. Eligible patients benefit from allo-SCT after response to the induction treatment. Cancer 2007. © 2007 American Cancer Society.